In defence of academic freedom: bioethics journals under siege. Issue 5 (1st May 2013) - Schüklenk, Udo
Abstract : This article analyses, from a bioethics journal editor's perspective, the threats to academic freedom and freedom of expression that academic bioethicists and academic bioethics journals are subjected to by political activists applying pressure from outside of the academy. I defend bioethicists' academic freedom to reach and defend conclusions many find offensive and 'wrong'. However, I also support the view that academics arguing controversial matters such as, for instance, the moral legitimacy of infanticide should take clear responsibility for the views they defend and should not try to hide behind analytical philosophers' rationales such as wanting to test an argument for the sake of testing an argument. This article proposes that bioethics journals establish higher-quality requirements and more stringent mechanisms of peer review than usual for iconoclastic articles.